The Graded Priming Effect of Semantic Radical on Chinese Character Recognition - Tong, Xiuhong; Xu, Mengdi; Zhao, Jing; Yu, Liyan (Frontiers in Psychology, 2021)
This study used priming paradigm with lexical decision task to examine the effects of different levels of semantic relatedness on the identification of Chinese phonetic–semantic compound characters. Unlike previous studies that simply classify Chinese compound characters as semantically transparent or opaque, we categorize the semantic relatedness between semantic radicals (i.e., prime) and the target characters containing them into five levels: highly related (i.e., high condition; e.g., prime ± vs. target 地), moderately related (i.e., moderate condition; e.g., prime ± vs. target 场), minimally related (i.e., minimal condition; e.g., prime ± vs. target 塔), unrelated but sharing the semantic radical (i.e., form-only condition; e.g., prime ± vs. target 坏), and unrelated without sharing the semantic radical (i.e., control condition; e.g., prime ± vs. target 涌). Moreover, three stimulus-onset asynchrony (SOA)s (i.e., 57, 140, and 243 ms) were used in this study to dissociate the radical- and character-level semantic priming effects. Results revealed a graded priming effect of the semantic radical on character recognition in Chinese readers for all SOAs. More specifically, the facilitative effect of the semantic radical on character processing was most evident for the high condition, followed by the minimal, form-only, and control conditions. This suggests a graded priming effect of the semantic radical on character identification.